Phytochemical Screening of White Turi (Sesbania grandiflora (L.) Pers.) Leaves Extract in Various Extraction Methods: Skrining Fitokimia Ekstrak Daun Turi Putih (Sesbania Grandiflora (L.) Pers.) pada Variasi Metode Ekstraksi - Rohmah, Jamilatur; Saidi, Ida Agustini; Rofidah, Luthfiyah; Novitasari, Fia; Margareta, Frida Amelia (Universitas Muhammadiyah Sidoarjo, 2021)
One of the Fabaceae family that has potential as medicinal plant is the white Turi plant (Sesbania grandiflora (L.) Pers.).The purpose of this study was to determine the content of secondary metabolites which can be extracted using a various extraction methods.The extraction method used are digestion, percolation, reflux, soxhlet, infusion, and decoction extraction. The Turi plants used come from Mojosari, Mojokerto.The results of the initial phytochemical screening of white Turi leaf extract (Sesbania grandiflora (L.) Pers.) Were extracts in six extraction methods containing alkaloids, saponins and tannins.In extracts using the digestion, soxhlet, and reflux method containing steroids.Meanwhile, the four extracts from the digestion, percolation, soxhlet, and reflux methods contain phenolic.And the infusion and decoction method extracts containing flavonoids and triterpenoids. The similarity of the phytochemical test results for each extract but with different intensity results.